The relationship between state-level factors and LGBTQ+ policies in diverse healthcare settings in the United States: a cross-sectional multilevel analysis - Hyunmin Yu; Stephen Bonett; Dalmacio Dennis Flores; Steven Meanley; Seul Ki Choi; Tari Hanneman; José A. Bauermeister (BMC Health Services Research)
Abstract Background Lesbian, gay, bisexual, transgender, queer or questioning, and other sexual and gender diverse (LGBTQ+) individuals face persistent discrimination in healthcare settings, highlighting organizational inclusion efforts to reduce these inequities. While prior research has largely focused on institutional characteristics, the broader policy and sociopolitical context in which healthcare facilities operate remains underexplored. This study makes a novel contribution by using a multilevel approach to examine how state-level factors (e.g., LGBTQ+ laws, political climate, racial and ethnic demographic composition, and Medicaid expansion) are associated with the implementation of LGBTQ+ inclusive policies and practices within diverse healthcare settings across the United States. Methods This cross-sectional study used the Healthcare Equality Index (HEI) data collected in 2021 to evaluate LGBTQ+ inclusion in healthcare facilities. We examined 904 American facilities across 48 states that participated in the HEI in 2021. Multilevel modeling was utilized to investigate the association between different state-level factors (LGBTQ+ inclusiveness in laws, political climate, racial and ethnic minority population, and Medicaid expansion status) and HEI scores in the domains of non-discrimination policies, LGBTQ+ inclusive clinical services, inclusive employee benefits, and LGBTQ+ community engagement within different types of healthcare facilities. Results In 48 states, 33.3% were Democratic, 22.9% were divided, and 43.8% were Republican; 70.8% had expanded Medicaid. The mean racial and ethnic minority population was 34.9% (SD = 16.2). Among the 904 facilities, 64.7% were short-term acute care hospitals. State-level political climate and racial and ethnic minority population were significant predictors of LGBTQ+ inclusive patient services within healthcare facilities. Compared to acute care hospitals, rehabilitation hospitals, Veterans Affairs (VA) hospitals, and outpatient facilities had lower scores for non-discrimination policies and LGBTQ+ staff training. VA hospitals scored higher for LGBTQ+ inclusive clinical services. Outpatient facilities, psychiatric and behavioral hospitals, and rehabilitation hospitals had lower scores for inclusive employee benefits, while VA hospitals scored higher. Critical access hospitals, psychiatric and behavioral hospitals, and VA hospitals had lower scores for LGBTQ+ community engagement. Conclusion Healthcare leaders must be mindful of the influence of state politics on the continued delivery of LGBTQ+ inclusive clinical services. Additionally, system-level interventions are needed to enhance LGBTQ+ inclusion efforts across various types of healthcare facilities.